2003
DOI: 10.1071/sr02076
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate retention under sugarcane in wet tropical Queensland deep soil profiles

Abstract: Nitrate leaching below the crop root-zone in variable charge soils may be adsorbed at anion exchange sites, thereby temporarily reducing the risk of contamination of water bodies. The objectives of this study were (i) to investigate whether nitrate adsorption, accumulation, and retention in the Johnstone River Catchment of Far North Queensland wet tropics is widespread; (ii) to assess the capacity of soil in the Johnstone River Catchment to retain nitrate; and (iii) to deduce the consequences of nitrate adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 11 publications
4
34
0
1
Order By: Relevance
“…While our results indicate that nitrate occupied a small proportion of anion exchange capacity (Fig. 6), substantial quantities of nitrate have accumulated under sugarcane at depths below 4 m in other Ferrosols in this region in contrast to native vegetation (Rasiah et al 2003).…”
Section: Discussionmentioning
confidence: 56%
“…While our results indicate that nitrate occupied a small proportion of anion exchange capacity (Fig. 6), substantial quantities of nitrate have accumulated under sugarcane at depths below 4 m in other Ferrosols in this region in contrast to native vegetation (Rasiah et al 2003).…”
Section: Discussionmentioning
confidence: 56%
“…The Ferrosols in the far-north Queensland's wet tropics possess the capacity (Rasiah et al, 2003a;Rasiah and Armour, 2001;Gillman and Abel, 1987) and have been found to retain large quantities of the nitrate leached below the root-zone (Rasiah et al, 2003a;Rasiah and Armour, 2001) However, the Ferrosols in this environment may contain considerable sulphate (Ayers and Manton, 1991;Douglas, 1968), which may limit the competitive adsorption of nitrate at anion exchange sites (Katou et al, 1996). Furthermore, the competitive anion adsorption at anion exchange sites is in the order sulphate>chlor-ide>nitrate (Katou et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…The leached nitrate might be adsorbed at anion exchange sites (Rasiah et al, 2003a;Rasiah and Armour, 2001), denitrify, and/or enter streams (Rasiah et al, 2003b). The retention and accumulation of the leached nitrate in soil matrix in this region is considered as advantageous, because the nitrate leaching below the crop root-zone could otherwise find its way into streams (Rasiah et al, 2003) and finally to the Great Barrier Reef (GBR) lagoon.…”
Section: Introductionmentioning
confidence: 98%
“…Not all applied nitrogen is utilised by the sugarcane crop (Thorburn et al 2003b), and losses of nitrogen from sugarcane production systems have been detected in surface water (Reghenzani et al 1996;Bengtson et al 1998;Ng Kee Kwong et al 2002) and groundwater (Rasiah et al 2003a(Rasiah et al , 2003bThorburn et al 2003a;Stewart et al 2006).…”
Section: Introductionmentioning
confidence: 99%